Knowledge of obstetric danger signs and its associated factors among pregnant women in Angolela Tera District, Northern Ethiopia - Gashaw Garedew Woldeamanuel; Gorems Lemma; Betregiorgis Zegeye (2019)
Knowledge of danger signs of obstetric complications is the first essential step in accepting appropriate and timely referral to maternal and newborn care units. The objective of this study was to assess the knowledge of obstetric danger signs and associated factors among pregnant women in Angolela Tera district, Northern Ethiopia. A community based cross sectional study was conducted among 563 pregnant women who were selected by multi-stage cluster sampling technique. Data were collected using a pre-tested and interviewer administered structured questionnaire. Descriptive statistics and binary logistic regression analysis were performed using statistical package for social sciences (SPSS) version 23.A total of 563 pregnant women were included in the study. About 211 (37.5%) women were knowledgeable about obstetric danger signs. Attending formal education, urban residence, time taken less than 20 min to reach health facility on foot, two or more history of pregnancies and receiving health education were found to be significantly associated with being knowledgeable about obstetric danger signs. A significant proportion of pregnant women in the study area were not knowledgeable about obstetric danger signs. Hence, continuous health education and appropriate counseling to pregnant mothers should be performed.